Hemostatic powder TC-325 as first-line treatment option for malignant gastrointestinal bleeding: a cost–utility analysis in the United Kingdom - Cooper, Dawn M.; Norton, Benjamin; Hawkes, Neil D; Hebbar, Srisha; Telese, Andrea; Morris, John; Haidry, Rehan; Barkun, Alan (Endoscopy, 2025)
Randomized controlled trials have shown that hemostatic powder (TC-325) results in greater immediate hemostasis and lower 30-day rebleeding rates than standard endoscopic therapy (SET) for management of malignant upper gastrointestinal bleeding (MUGIB). We explored whether TC-325 would be a cost-effective first-line option for patients with MUGIB compared with SET in the United Kingdom.A decision tree was developed for patients with MUGIB, assessing initial therapy with TC-325 or SET over a 30-day period. Patients with failed initial hemostasis or a rebleed within 30 days underwent further endoscopic treatment, escalation to either transcatheter arterial embolization or surgery, or radiotherapy. Overall 30-day mortality was applied. Costs, in GBP, were based on the United Kingdom National Health Services costs for 2023/2024. Results were reported as incremental differences in cost, quality-adjusted life years (QALY), and net monetary benefit. Deterministic and probabilistic sensitivity analyses and scenario analyses were performed.The cost of treating MUGIB patients with TC-325 was £245.88 lower than treatment with SET, with an incremental increase of 0.001 QALYs. TC-325 remained a cost-saving approach in sensitivity and scenario analyses. Probabilistic sensitivity analysis revealed that TC-325 was more effective and cost saving in 80.1% of simulations (range 67.5%–98.63%).Initial treatment of MUGIB with TC-325 compared with SET was more effective (higher primary hemostasis and lower 30-day rebleeding) and cost saving owing to the requirement for fewer interventions, readmissions, and length of stay. Additional studies are needed to address model uncertainties in the follow-up management of these complex patients.